2018
DOI: 10.5336/sportsci.2017-57533
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels, BMI and Healthy Life Style Behaviors in Adolescents Living in a Rural District

Abstract: A AB BS S T TR RA AC CT T OOb bj je ec ct ti iv ve e: : Getting insight into pubescent health behaviors and related aspects is the initial step in improving lifelong health. The purpose of this study was to examine the relationship among physical activity levels (PALs), body mass index (BMI) and healthy lifestyle behaviors (HLBs) in adolescents in one of the rural districts of Turkey. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Participants were 749 14-18-year-old Turkish girls and boys in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
3
2
Order By: Relevance
“…Some studies have shown that there is a relationship between HLSB and BMI [21][22][23]; however, we did not find any relationship between BMI and components of HLSB similar to Esatbeyoğlu and Isler [24]. Previous studies have also shown that there is a relationship between cognitive beliefs about leading a healthy lifestyle, including attitudes and intended choices, and PA as well as nutritional rewards [25].…”
Section: Discussioncontrasting
confidence: 75%
“…Some studies have shown that there is a relationship between HLSB and BMI [21][22][23]; however, we did not find any relationship between BMI and components of HLSB similar to Esatbeyoğlu and Isler [24]. Previous studies have also shown that there is a relationship between cognitive beliefs about leading a healthy lifestyle, including attitudes and intended choices, and PA as well as nutritional rewards [25].…”
Section: Discussioncontrasting
confidence: 75%
“…Adolescents' PA (16.08±3.76) (Kaya et al, 2016) subgroup in one study and PLP (18.28±2.93) (Turan et al, 2021) subgroup in another study had lower scores than this study. In two studies HR (11.21±2.63, and 12.56±2.56, respectively) (Esatbeyoğlu & Kin İşler, 2018;Turan et al, 2021), in another study SM (17.62±2.74) and SH (17.09±3.02) (Turan et al, 2021), and PLP subgroup (25.74±3.30) (Esatbeyoğlu & Kin İşler, 2018) in another study seem to have higher scores than this study. Since these various results were studied with different sample groups, it can be said that this is an expected situation.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, there were also some studies that total ALP, HR, SH (Sousa et al, 2015), HR, PLP, SM (Ardic & Esin, 2016), HR (Karagözoğlu, 2021) and PLP, IR (Çiçek & Çetinkaya, 2017) scores were higher in females than males. However, it was seen that total ALP and subscale scores did not differ according to gender in studies of Kaya et al (2016) and Esatbeyoğlu and Kin İşler (2018). In studies using different scales, it was observed that scale scores in various dimensions differed according to gender (Aktaş Özakgül et al, 2016;Bebiş et al, 2015;Coşkun & Karagöz, 2021;Karadamar et al, 2014;Kazak et al, 2021;Turan et al, 2021;Yaşar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that VI reduces quality of life (Jones et al, 2019; Siira et al, 2019), whereas PA participation promotes quality of life (Esatbeyoglu & Kin İsler, 2018; Gill et al, 2013) and provides health-related benefits for individuals with VI (Furtado et al, 2016; Giese et al, 2017). It can be suggested that PA manages body composition, promotes postural balance ability, and reduces BMI in individuals with VI.…”
Section: Introductionmentioning
confidence: 99%